A customizable aluminum compensator system for total body irradiation. Issue 10 (25th August 2021) - Naessig, Madison; Hernandez, Soleil; Astorga, Nestor Rodrigo; McCulloch, James; Saenz, Daniel; Myers, Pamela; Rasmussen, Karl; Stathakis, Sotirios; Ha, Chul S.; Papanikolaou, Niko; Ford, John; Kirby, Neil
Abstract: Purpose: To develop a simplified aluminum compensator system for total body irradiation (TBI) that is easy to assemble and modify in a short period of time for customized patient treatments. Methods: The compensator is composed of a combination of 0.3 cm thick aluminum bars, two aluminum T‐tracks, spacers, and metal bolts. The system is mounted onto a plexiglass block tray. The design consists of 11 fixed sectors spanning from the patient's head to feet. The outermost sectors utilize 7.6 cm wide aluminum bars, while the remaining sectors use 2.5 cm wide aluminum bars. There is a magnification factor of 5 from the compensator to the patient treatment plane. Each bar of aluminum is interconnected at each adjacent sector with a tongue and groove arrangement and fastened to the T‐track using a metal washer, bolt, and nut. Inter‐bar leakage of the compensator was tested using a water tank and diode. End‐to‐end measurements were performed with an ion chamber in a solid water phantom and also with a RANDO phantom using internal and external optically stimulated luminescent detectors (OSLDs). In‐vivo patient measurements from the first 20 patients treated with this aluminum compensator were compared to those from 20 patients treated with our previously used lead compensator system. Results: The compensator assembly time was reduced to 20–30 min compared to the 2–4 h it would take with the previous lead design. All end‐to‐end measurements were within 10% of that expected. The median absolute in‐vivo error for the aluminum compensator was 3.7%, with 93.8% of measurements being within 10% of that expected. The median error for the lead compensator system was 5.3%, with 85.1% being within 10% of that expected. Conclusion: This design has become the standard compensator at our clinic. It allows for quick assembly and customization along with meeting the Task Group 29 recommendations for dose uniformity.